A Survey of the Use of Ultrasound by Upper Extremity Surgeons. (January 2017) - Wang, William L.; Kruse, Kevin; Fowler, John R.
Background: Ultrasound is a versatile imaging modality that can be used by upper extremity surgeons for diagnostic purposes and guided injections. The perceptions of ultrasound for diagnosis and treatment among upper extremity surgeons and its barriers for adoption have not been formally surveyed. The purpose of this study is to determine the current usage of musculoskeletal ultrasound for diagnostic purposes and guided injections by upper extremity surgeons and their reasons for using it or not using it in practice.Methods: A 22-question survey was distributed to the American Society for Surgery of the Hand (ASSH). The survey questions consisted of respondent characteristic questions and questions pertaining to the use of ultrasound. Chi-square analysis was performed to assess for a difference in ultrasound usage across respondent characteristics.Results: Three hundred four (43%) answered that they have an ultrasound machine in their office; Fifty-one percent (362) of the respondents use ultrasound for diagnostic purposes. Fifty-five (8%) of the survey respondents use ultrasound to diagnose carpal tunnel syndrome; 168 (23.5%) respondents reported that they use ultrasound for guided injections. There was a statistically significant difference between access to an ultrasound machine in the office by practice setting and use of ultrasound for diagnostic purposes by practice setting.Conclusions: The use of ultrasound by upper extremity surgeons is split for diagnostic purposes, with fewer surgeons using ultrasound to diagnose carpal tunnel syndrome and guided injections. Ultrasound machine availability and the use of ultrasound for diagnosis appear to be influenced by practice setting.